2021
DOI: 10.1097/fjc.0000000000001031
|View full text |Cite
|
Sign up to set email alerts
|

Circ-PRKCI Alleviates Lipopolysaccharide-induced Human Kidney 2 Cell Injury by Regulating miR-106b-5p/GAB1 Axis

Abstract: Circular RNAs act as vital regulators in diverse diseases.However, the investigation of circular RNAs in sepsis-engendered acute kidney injury remains dismal. We aimed to explore the effects of circular RNA protein kinase C iota (circ-PRKCI) in lipopolysaccharide (LPS)-mediated HK2 cell injury. Sepsis in vitro model was established by LPS treatment. Quantitative real-time polymerase chain reaction assay was conducted for determining the levels of circ-PRKCI, microRNA-106b-5p (miR-106b-5p), and growth factor re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Up to now, accumulating evidence has indicated that exceptionally expressed circRNAs are implicated in the development of sepsis‐associated AKI. For instance, circVMA21 or circPRKCI overexpression 25,26 and circFANCA silencing 27 are capable of inhibiting apoptosis and inflammation in LPS‐stimulated septic AKI in a ceRNA manner. Our study for the first time demonstrated that circITCH was underexpressed in serum of patients with sepsis‐induced AKI and LPS‐induced HK‐2 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, accumulating evidence has indicated that exceptionally expressed circRNAs are implicated in the development of sepsis‐associated AKI. For instance, circVMA21 or circPRKCI overexpression 25,26 and circFANCA silencing 27 are capable of inhibiting apoptosis and inflammation in LPS‐stimulated septic AKI in a ceRNA manner. Our study for the first time demonstrated that circITCH was underexpressed in serum of patients with sepsis‐induced AKI and LPS‐induced HK‐2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Up to now, accumulating evidence has indicated that exceptionally expressed circRNAs are implicated in the development of sepsis-associated AKI. For instance, circVMA21 or circPRKCI overexpression 25,26 28 gastric cancer, 29 osteosarcoma, 30 and glioma 31 as well as nasopharyngeal carcinoma. 32 The cardioprotective effects of circITCH against H 2 O 2 or doxorubicin-induced myocardial injury were recently reported by Zhang et al 19 and Han et al, 20 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies had shown that many newly discovered circRNAs were involved in the regulation of AKI caused by sepsis (31). For instance, overexpression of circ-PRKCI upregulated GAB1 by combining miR-106b-5p to inhibit LPS damage to HK-2 cells, including inhibition of apoptosis, inflammation, and oxidative stress (13). It was known that circUSP42 was downregulated in the serum of patients with AKI caused by sepsis (20), but the function and regulation mechanism of circUSP42 needed to be explored in depth.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating studies constructed sepsis-induced AKI cell models with LPS treatment and asserted that inflammatory response, oxidative stress, and other body responses that are extremely related to the development of AKI (10), which were participated by a variety of molecules, including circRNAs (11). Numerous evidences indicated that circRNAs, as competitive endogenous RNA, regulated target gene expression at the transcription and translation level via combining miRNAs to participate in the progress of AKI (12)(13)(14). For example, circ-FANCA knockdown reduced the damage of HK2 cells induced by LPS by regulating the miR-93-5p/OXSR1 axis (15).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, circ-PRKCI was decreased in patients with septic AKI and in LPS-simulated HK-2 cells. Circ-PRKC1 likely acts as a sponge for miR-106b-5p to regulate the expression of growth factor receptor binding 2-associated binding protein 1 (GAB1), a protein that has been associated with tissue damage in acute lung injury; the overexpression of circ-PRKCI had salutary effects on cell apoptosis and inflammation [ 41 ]. In a rat CLP model of septic AKI, circ-Ttc3 was downregulated in kidney samples with the resultant overexpression of miR-148a.…”
Section: Circrna Expression In Aki Due To Sepsismentioning
confidence: 99%